2017
DOI: 10.1515/ijicte-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Attitudes Toward Game-based Learning in History Education

Abstract: Game-based learning (GBL) is an emerging field reaching new contexts. Research has reported about students' rich use of digital games and the learning potential of GBL in traditional school subjects. Digital games have been tested as educational tools in various subjects in Swedish schools during the last decade, in areas such as teaching and learning of history and foreign languages. However, there is a lack of detailed research on attitudes toward the use of GBL in history education.Main aim of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Regarding the financial resources, the cost of purchasing games and the lack of financial support are linked to outdated technology infrastructure in schools and therefore, limited budgets appear to be the most crucial inhibiting factor for implement DGBL. Thus, according to teachers’ opinion, despite their positive attitudes and their intention to use digital games for teaching, it is assumed that there will be insufficient financial support (Baek, 2008 ; Klemetti et al, 2009 ; Li, 2017 ; Mozelius et al, 2017 ; Wu, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the financial resources, the cost of purchasing games and the lack of financial support are linked to outdated technology infrastructure in schools and therefore, limited budgets appear to be the most crucial inhibiting factor for implement DGBL. Thus, according to teachers’ opinion, despite their positive attitudes and their intention to use digital games for teaching, it is assumed that there will be insufficient financial support (Baek, 2008 ; Klemetti et al, 2009 ; Li, 2017 ; Mozelius et al, 2017 ; Wu, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researcher found that students' attitude toward game-based learning platform is mostly positive (Bicen & Kocakoyun, 2018;Chaiyo & Nokham, 2017;Correia & Santos, 2017;Licorish et al, 2018;Plump & LaRosa, 2017). From the perspective of the teacher, Mozelius, Hernandez, Sällström, & Hellerstedt (2017) found that teacher attitude toward game-based learning is positive. However, there are so many obstacles to implementing online game-based learning in the classroom, such as the internet facility, the ability of the teacher to operate the computer, and the devices used for the learning.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the use of game-based learning from the teacher's perspective. Study from Mozelius, Hernandez, Sällström, & Hellerstedt (2017) found that teacher attitude toward game-based learning is positive. Although the teacher's view of game-based learning is positive, the implementation of game-based learning is still limited, and it needs a serious study of how to create it more accessible and useful for teachers (Razak, Connolly, & Hainey, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…As indicated by Mozelius et al (2017), a simulation game denotes a board game, or those various teacher-made games for teaching and learning purposes. The focus of these pedagogical games is usually on the socioeconomic, religious, political and aspects of society.…”
Section: Simulation-game Pedagogical Strategymentioning
confidence: 99%
“…Antunes et al (2012) contend that simulation games are applied in the teaching-learning process because they provide fascinating challenges to learners and add interest, activity and novelty to the lesson. According to Mozelius et al (2017), it increases their enthusiasm and leads to learning outcomes.…”
Section: Simulation-game Pedagogical Strategymentioning
confidence: 99%